ANALISIS FAAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN SEPEDA MOTOR MEREK HONDA - Erliyanto, 08.05.51.0025 Eko; Widyasari, Suzy (Students Journal of Economic and Management, 2012)
With so manyautomotive companiesinIndonesia, then the consumerwill be moreselectivein decidingwhichbrand ofmotorcycleis usedas ameans of transportation. The emergence of Chinesemotorcycle manufacturerofthemotorcycleindustryto tightencompetitioninIndonesia. This studyaimedtoanalyze the influence ofthevariabel-variabel may have onconsumerpurchase decisionsinbuying Hondamotorcyclein the city areaPurwodadi, Kab. Grobogan, Central Java.There are four hypotheses to be tasted in this study, this hipothesis will test the effectsanalysis of product quality, brand image, price perceptions and promotion on purchasedecisions of Honda motorccycles. The samples used inthis study80respondentswith apurposivesamplingtechnique is a technique samplingby taking asamples withspesificcriteria. The dataused arethe primary dataand secondarydata analysis was qualitativeanalysisand thecoefficient of determination, totest the hypotheses usingttest. Based on data analysis and hypothesis testing can be concluded that the partially variable product quality, brand image, price perceptions and promotion has a significant and positive influence on purchase decisions of Honda motorcycles.Most dominant variable in this study is the variable product quality while the coefficient of determination can be in the know that the variable product, brand image, price perceptions and promotion are able to explain the variation of 57.3% for the remainder of the purchase decision is influenced by a 43.7% other variables that were not analyzed in this study. Key words: Product quality, Brand Image, Price Perseptions, Promotion and Purchase Decisions